Anti–3‐hydroxy‐3‐methylglutaryl‐coenzyme a reductase necrotizing myopathy masquerading as a muscular dystrophy in a child. Issue 6 (25th April 2017) - Mohassel, Payam; Foley, A. Reghan; Donkervoort, Sandra; Fequiere, Pierre R.; Pak, Katherine; Bönnemann, Carsten G.; Mammen, Andrew L.
ABSTRACT: Introduction: Immune‐mediated necrotizing myopathies (IMNMs) are characterized by progressive weakness, elevated serum creatine kinase levels, and necrotizing myopathic features on muscle biopsy. Presence of highly specific autoantibodies against signal recognition particle (SRP) or 3‐hydroxy‐3‐methylglutaryl‐ coenzyme A reductase (HMGCR) can aid in recognition and confirmation of IMNMs. Methods: In this study we describe a boy with HMGCR‐positive necrotizing myopathy and highlight the clinical features of the patient. Results: In contrast to most adults, the patient described had a more indolent disease course, reminiscent of a muscular dystrophy. Intravenous immunoglobulin monotherapy resulted in a dramatic clinical response with return to normal strength. Conclusions: Systematic consideration of IMNMs and testing for relevant autoantibodies in children with suspected but genetically unconfirmed muscular dystrophy may help improve diagnostic accuracy and allow timely treatment with potentially highly effective immunotherapies. Muscle Nerve 56 : 175–179, 2017